(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
The present case study was carried out to evaluate the role of Uttar basti with in tubal blockage, in order to establish it as a safer and cost effective Ayurvedic treatment modality. The criteria for selection of tubal blockage diagnosed in diagnostic laproscopy. Uttar basti was administered, after cessation of menstruation, to the screened patient through hematological, urinary and serological (HIV, VDRL, HBsAG) investigations. The result suggests that Uttar basti is a highly significant treatment for tubal blockage. Uttar basti is ideal local therapy is to be adopted in tubal block. Apamarga ksar tail is very good Vata kaphashamak guna and Lekhan properties, Taila is having the property to reach minute channels in body. Phala ghruta is best for all Yonirogas, also to reduce Dhaha which is due to Kshar tail.